Parâmetros físico-químicos, qualidade microbiológica e sensorial da carne de cabritos alimentados com diferentes dietas e abatidos aos 60 dias de idade - Assis, Ana Paula Pinheiro de (Universidade Federal Rural do Semi-Árido, 2014)
The objective of thisstudywastoevaluatethephysico- chemical parameters of meat quality of goats feddifferentliquid diets until 60 days of life , in additiontoperformingmicrobiological and sensoryanalysis of meat of theseanimals . 24 male goats , SPRD , distributed in a completelyrandomized design withthreetreatments and eightreplicateswereused : goat milk ( control ) ; Bovinemilk ; 50 % bovinemilk + 50 % Serumcheese. The animalswereslaughtered at 60 days . PH measurements at roomtemperature and after 24 hours of slaughter (- 30 minutes and pH24h - pH0 24 hours) weretaken color parameters ( L *, a *, b *) , waterretentioncapacitywerestudied (CRA ) , weightlossduringcooking ( PPC ) , shear force ( FC ) , wateractivity ( Aw ) , themoisture , protein, lipid and ashwereobtained . Sensory quality wasevaluatedbyapplying a test of acceptance and purchaseintent , and for microbiologicalanalysis , samplesweresubjectedtothedetermination of thermotolerantcoliforms , Salmonella spp . and Staphylococcus Coagulase Positive . The muscle used for theanalysiswasthe ribeye . Data wereanalyzedby General Linears Models procedure ( GLM ) of thestatisticalpackage SAS , and meanswerecomparedby Tukey test at 5%. The average pH of the carcass after slaughter pH0 was 6.3 and 5.5 pH24h . Therewas no significantdifferencebetweenthetemperatures of hot carcass and cold carcass , meat of animalsfedthedifferent diets . The sampleshadlowervalues for L * (brightness) and upwardsonthecoordinate b * (yellow). The meat of the goat milk diet retained more water . The meat of themilk + whey diet hadlessweightlossduringcooking and lowershear force . The slaughter age and thedifferentliquid diets interferedsignificantly ( P < 0.05 ) in moisture, protein and lipids . Microbiologicalanalysisshowedthatthesamplesmetthemicrobiological standards for fresh beef . Sensoryanalysisshowedthat meat from the goats gotanappropriateacceptance rate , correspondingtothethird and fourthlevels of thehedonicscale ( moderatelyliked and likedslightly ) . The characteristicsthatmostinfluencedtheacceptance of theproductwerethe color ( 7.58 ) , followedbytenderness ( 7.30) . The age of slaughter of animals at 60 dayscanbeusedtoproducebetter quality meat , significantlyimprovingthephysicalattributes - chemical , microbiological and sensory meat
Physical-chemical parameters, microbiological and sensory quality beef and kids fed different diets and slaughtered at 60 days of age
Keywords: Goats; Color; Shear force; Lipids; Proteins; Caprinos; Cor; Força de cisalhamento; Lipídeos; Proteínas; CIENCIAS AGRARIAS::MEDICINA VETERINARIA